HUBUNGAN ANTARA POLA PEMBERIAN MAKANAN PENDAMPING ASI (MP-ASI) DAN STATUS GIZI BALITA USIA 6-24 BULAN DI WILAYAH KERJA PUSKESMAS GEDONGTENGEN YOGYAKARTA - Septiana, Rika; Djannah, Sitti Nur; Djamil, M Dawam (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2010)
Background: Economic crisis had happened since 1997 till now still not be overcome yet carefully. This had caused more number of poor families and declined purchasing power of food. Furthermore, the availability of foods in family becomes limited in the end generates the potency of less consumption of nutrient to malnutrition. Malnutrition is primary factor causing baby and child under fifth age mortality. Malnutrition normally caused by two primary factors namely by disease infection and the lack of nutrient as a result by lack of the availability of food in household level or wrong taking care manner. The giving of not accurately food can caused malnutrition and excessive nutrient can caused obesity. At the age of 6 month, physiologically, baby has ready to receive additional food, because at that age the mothers milk shall no longer fulfill for the baby to grow, so that feeding the complementary food of mothers milk is hardly required. So that complementary food for mothers milk hardly required. Purpose of this research was to understand the relationship between feeding pattern of complementary food and nutrition status of child under fifth age at range of 6-24 months in Puskesmas Gedongtengen Yogyakarta region.Method: This was an observational research using cross-sectoanal approach. The variables that involved in this research are the pattern of complementary feeding for mothers milk as an independent variable and nutrition status of child under fifth age between 6-24 months as a dependent variables. This research executed in March until April 2009 with sample amount 74 child under fifth age. Retrieval of data applies semi qualitative food frequency questionary (SQFFQ). Result of this research analyzed by chi square test.Result: Result of this research indicates that giving pattern of complementary feeding for mothers milk seen from consumption level of energy included in good category ( 91,89%), and nutrition status in normal category is 57 child under fifth age ( 77,03%), while 16 of child under fifth age samples is in abnormal category ( 22,97%). The analysis result of complementary feeding pattern for mothers milk and nutrition status of child under fifth age , 6-24 months shows the Chi-Square value 4,103 with a significant level of 0.043 (p <0.05).Conclusion: There was a meaningful relationship between the pattern of complementary feeding for mothers milk and nutrition status of child under fifth age 6-24 months in Puskesmas Gedongtengen Yogyakarta region.Keywords: complementary feeding for mothers milk, nutritional status, child under fifth age.